2008
DOI: 10.1093/europace/eun021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in individuals with cardiovascular implantable electronic devices

Abstract: Magnetic resonance (MR) imaging has unparalleled soft-tissue imaging capabilities. The presence of devices such as pacemakers and implantable cardioverter-defibrillators (ICDs), however, was historically considered a contraindication to MR imaging. We summarize the potential hazards of the device-MR environment interaction, and present updated information regarding in vitro and in vivo experiments suggesting that certain pacemaker and ICD systems may indeed be MR-safe. Recent reports on several hundred patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
167
1
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(190 citation statements)
references
References 50 publications
0
167
1
22
Order By: Relevance
“…However, various studies in the last 15 years have been able to show that it is possible to perform MR examinations with an acceptable level of risk in patients with conventional PM/ICD systems taking into consideration the individual risk/benefit profile as a single-case decision and as "off-label" use and applying specific safety precautions [1 -20]. In 2008, a European position paper regarding this topic with participation of corresponding expert groups from cardiology and radiology was published and the presence of PM/ICD systems was newly classified as a relative MR contraindication [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, various studies in the last 15 years have been able to show that it is possible to perform MR examinations with an acceptable level of risk in patients with conventional PM/ICD systems taking into consideration the individual risk/benefit profile as a single-case decision and as "off-label" use and applying specific safety precautions [1 -20]. In 2008, a European position paper regarding this topic with participation of corresponding expert groups from cardiology and radiology was published and the presence of PM/ICD systems was newly classified as a relative MR contraindication [1].…”
Section: Introductionmentioning
confidence: 99%
“…Where it contained 50% to 75% of these patients, it developed indications for MRI during their devices and showed that every year, approximately 200 000 patients with pacemakers or ICDs, MRI was rejected (Roguin et al 2008).…”
Section: Background Of the Studymentioning
confidence: 99%
“…A mágneses rezonanciás (MR-) készülékek fejlődésének köszönhetően egy jó felbontású MR-készülékkel sokkal részletesebb és pontosabb szubsztrátkeresés valósítható meg. A gond, hogy sok betegnél a már beültetésre került ICD-készülék miatt az intézetek nem végzik el a szív-MR-vizsgálatot, holott ennek biztonságossága -megfelelő programozással 1,5 T-ig -igazolt [16]. A komputertomográfi ás (CT-) vizsgálatoknak inkább a koszorúér-betegségek nem invazív diagnosztikájában van kiemelkedő szerepe, de az utóbbi években az ECHO-és MR-képalkotók mellett egyre nagyobb szerepet kap a myocardium betegségeinek diagnosztikájában [17].…”
Section: Képalkotó Eljárásokunclassified